2011
DOI: 10.1017/jfm.2011.366
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow in a rotating torus after a sudden change in rotation rate

Abstract: We consider the temporal evolution of a viscous incompressible fluid in a torus of finite curvature; a problem first investigated by Madden & Mullin (J. Fluid Mech., vol. 265, 1994, pp. 265-217). The system is initially in a state of rigid-body rotation (about the axis of rotational symmetry) and the container's rotation rate is then changed impulsively. We describe the transient flow that is induced at small values of the Ekman number, over a time scale that is comparable to one complete rotation of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
6
19
0
Order By: Relevance
“…For the BDF2 method, this composite solution is assumed at times of t = ∆t and t = 2∆t (where ∆t is the computational time step, typically 0.005) then computation determines the subsequent evolution for t = n∆t, n = 3, 4, · · · . This approach has been used in other comparable impulsive boundary-layer problems with some success, such as Hewitt et al (2011). Spatial adaptivity is employed to accurately resolve the fine near-wall structures and results presented herein have been confirmed to be converged by repeated computation over different spatial-temporal refinements.…”
Section: A Two-dimensional Finite Re Formulationmentioning
confidence: 78%
“…For the BDF2 method, this composite solution is assumed at times of t = ∆t and t = 2∆t (where ∆t is the computational time step, typically 0.005) then computation determines the subsequent evolution for t = n∆t, n = 3, 4, · · · . This approach has been used in other comparable impulsive boundary-layer problems with some success, such as Hewitt et al (2011). Spatial adaptivity is employed to accurately resolve the fine near-wall structures and results presented herein have been confirmed to be converged by repeated computation over different spatial-temporal refinements.…”
Section: A Two-dimensional Finite Re Formulationmentioning
confidence: 78%
“…Eruptions resulting from finite-time singularities can also occur at both inner and outer radii, albeit at different times, if the direction of rotation is changed impulsively. Hewitt et al (2011) provided strong evidence that this finite-time singularity coincided with the development of an observable band in the top-down flow visualisation experiments of Madden & Mullin (1994).…”
Section: Introductionmentioning
confidence: 77%
“…For example, when the finite-time singularity manifests at point A in the Madden & Mullin (1994) experiment, a second laminar band is also observed at point B. Hewitt et al (2011) showed that the boundary layers on the opposite equator were subject to an axisymmetric centrifugal instability that could be triggered by an isolated wall perturbation. Furthermore, for typical laboratory flows, it was found that the time scales of this centrifugal instability and the boundary-layer eruption were similar.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations